2014
DOI: 10.1155/2014/595962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotics Supplementation on Bone Mineral Content and Bone Mass Density

Abstract: A few studies in animals and a study in humans showed a positive effect of probiotic on bone metabolism and bone mass density. Most of the investigated bacteria were Lactobacillus and Bifidobacterium . The positive results of the probiotics were supported by the high content of dietary calcium and the high amounts of supplemented probiotics. Some of the principal mechanisms include (1) increasing mineral solubility due to production of short chain fatty acids; (2) producing phytase enzyme by bacteria to overco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 36 publications
1
59
1
1
Order By: Relevance
“…This protection was associated with altered pro-osteoclastogenic cytokines 28 . In contrast, in a rat Ovx model, Parvaneh et al showed that Bifidobacterium longum supplementation increased BMD, but rather than decreasing bone resorption markers they observed an increase in bone formation 29,30 .…”
Section: Manipulation Of the Microbiota With Probiotics: Effects On Bmentioning
confidence: 92%
“…This protection was associated with altered pro-osteoclastogenic cytokines 28 . In contrast, in a rat Ovx model, Parvaneh et al showed that Bifidobacterium longum supplementation increased BMD, but rather than decreasing bone resorption markers they observed an increase in bone formation 29,30 .…”
Section: Manipulation Of the Microbiota With Probiotics: Effects On Bmentioning
confidence: 92%
“…Consistent with this, Sjogren et al found that bacterial colonization of young adult GF animals resulted in loss of trabecular bone mass and an increase in bone-resorbing osteoclasts (13). However, other studies have suggested that treatment with beneficial microbes modestly increases bone mineral density (21)(22)(23)(24)(25)(26) and protects against bone loss after sex steroid deficiency (27). Discrepant results in studies examining the effect of microbiota on bone may reflect differences in the composition of the resident microbiota, age of the animal at colonization and necropsy, mouse strain, and sex.…”
mentioning
confidence: 87%
“…Furthermore, it was reported that bifidobacteria treatment increased bone Ca content and bone strength together with increased cecal propionate concentration in normal rats [23]. One of the mechanisms for the bone-effect of probiotics was considered to be due to increased mineral solubility by the production of SCFAs [24]. Indeed, the present study showed that B-HD treatment prevented reduction of serum Ca levels, whereas a significant reduction was observed in Nx + placebo.…”
Section: Discussionmentioning
confidence: 43%